Government credit and trade war - Ning Cai; Jinlu Feng; Yong Liu; Hong Ru; Endong Yang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
By merging transaction-level trade data from China Customs and loan data from the China Development Bank (CDB), we analyze the effects of government credit on trade activities. We find that CDB credit mainly flows to SOEs in strategic industries at the top of the supply chain. These up-stream loans lead to the lower price and higher amount of export goods of private firms in down-stream industries, which leads to decreases in employment and performance of the US firms in the same industry. In contrast, the US firms in downstream industries use cheaper intermediate goods imported from China and perform better subsequently.
URN:NBN:fi:bof-201904251160
Keywords: E51; F30; G21; G28; 330; government credit; export; supply chain; trade war